EVALUASI IMPLEMENTASI HUKUM KESEHATAN DI ERA PANDEMI COVID-19: TANTANGAN DAN SOLUSI - Gunawan Widjaja (CV. Adiba Aisha Amira, 2025)
The implementation of health law during the COVID-19 global crisis revealed significant challenges, such as limited health infrastructure, bureaucratic obstacles, and inequitable access to medical services. Nonetheless, this situation has also encouraged the creation of innovative solutions, including capacity building of health facilities, adoption of telemedicine technology, and flexible policies tailored to emergency needs. Hence, the importance of cross-sectoral cooperation and community involvement in dealing with health crises. As such, this pandemic provides important insights into the future preparedness and adaptability of health legal systems.